2008
DOI: 10.1667/rr0732.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Relative Risks for Cancers in a Population after Prolonged Low-Dose-Rate Radiation Exposure: A Follow-up Assessment from 1983 to 2005

Abstract: Radiation effects on cancer risks in a cohort of Taiwanese residents who received protracted low-dose-rate gamma-radiation exposures from (60)Co-contaminated reinforcing steel used to build their apartments were studied, and risks were compared to those in other radiation-exposed cohorts. Analyses were based on a more extended follow-up of the cohort population in which 117 cancer cases diagnosed between 1983 and 2005 among 6,242 people with an average excess cumulative exposure estimate of about 48 mGy. Cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 35 publications
5
37
0
Order By: Relevance
“…Exposure information was obtained from personal monitoring data in most occupational settings, although monitoring may have been incomplete or highly uncertain in some studies 22 26. Personal monitoring data were not available for environmental studies; thus, doses were estimated using complex dosimetry systems 19 21 28…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure information was obtained from personal monitoring data in most occupational settings, although monitoring may have been incomplete or highly uncertain in some studies 22 26. Personal monitoring data were not available for environmental studies; thus, doses were estimated using complex dosimetry systems 19 21 28…”
Section: Resultsmentioning
confidence: 99%
“…1. Hwang et al 19 examined leukaemia incidence in a cohort of Taiwanese residents (n=6242) exposed between 1983 and 1992 from52 Co-contaminated reinforcing steel used to construct their dwellings 19. Only six incident leukaemias occurred in a cohort whose average excess cumulative exposure was less than 50 mGy (range: <1–2363).…”
Section: Discussionmentioning
confidence: 99%
“…Such factors are characterized by the ability of specific influencing and modifying cell genetic material. In the case of CML, ionizing radiation and benzene exposure, together with its main metabolite catechol, have been identified as risk factors [29][30][31][32][33]. On the other hand, CLL has not been connected with environmental risk factors [29,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of CML, ionizing radiation and benzene exposure, together with its main metabolite catechol, have been identified as risk factors [29][30][31][32][33]. On the other hand, CLL has not been connected with environmental risk factors [29,[34][35][36]. Presently, many authors think that exposure to ionizing and nonionizing radiation such as electric or electromagnetic fields and long-term exposure to chemical substances used in hair dyes production or mortar construction kits correlate positively with a higher risk of CLL [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the reported cancer incidence among the residents of apartments in Taiwan who were subjected to LDR from contaminated building materials (Hwang et al, 2006;Hwang et al, 2008) has shown a reduced overall cancer incidence in the radiated cohort in comparison to an age-matched control group (Doss, 2013).…”
Section: Recent Data Negate Carcinogenic Concerns Regarding Low Dose mentioning
confidence: 99%